Burnout in healthcare education programs and English as a Medium of Instruction: the dark side of the language of instruction - Munassir Alhamami (Frontiers in Medicine)
BackgroundCurrent research findings show that students in healthcare education programs face high levels of burnout. When English is used as the Medium of Instruction (EMI), non-native speakers experience added linguistic strain, increasing their stress, cognitive overload, and emotional exhaustion.PurposeThis study explores the relationship between EMI and student burnout in undergraduate healthcare education programs in Saudi universities. It examines how EMI affects students’ emotional well-being, academic engagement, and sense of efficacy.MethodsA mixed-methods approach was used. Quantitative data were collected from 213 students using a burnout scale measuring four constructs: exhaustion, cynicism, academic efficacy, and disengagement. Qualitative data were gathered from open-ended responses, with thematic analysis guided by Maslach’s burnout framework.ResultsQuantitative results showed high levels of exhaustion and disengagement, while cynicism and reduced efficacy were at moderate levels. Strong correlations were found between burnout dimensions, particularly between exhaustion, cynicism, and disengagement. Qualitative findings revealed that EMI caused emotional exhaustion due to linguistic overload, academic detachment from repeated failure, and reduced self-confidence in students’ academic skills. Many students expressed frustration, identity loss, and a desire to withdraw from their programs due to the use of EMI.ConclusionThe findings indicate that EMI can contribute significantly to student burnout in healthcare education. Without adequate language support and institutional adjustments, EMI may negatively affect students’ mental health, academic performance, and motivation. The study calls for more inclusive EMI practices that address students’ linguistic needs while protecting their well-being and academic success.